Síntese e caracterização de hidróxidos duplos a partir da lama vermelha - CUNHA, Márcia Valéria Porto de Oliveira (2015)
Bauxite refinery residues, commonly known as "red mud", have been shown to be capable of binding trace metals such as copper, cadmium, zinc, chromium, nickel and lead under suitable conditions. Neutralization of red mud is necessary because red muds are typically highly caustic, with a reaction pH of about 13. Much research has been carried out on utilization of red mud because it contains a lot of valuable components. Although utilization of the red mud as building material and as an absorbent is attractive because the red mud is used in bulk, nothing can be done without discarding valuable components such as titanium, zirconium and the main iron. Hydrotalcite-synthesis connected with recycling of alkali-solution is a prospective way for effective use of the solution under the strong demand for the environmental protection in the world. The hydrotalcite-like compounds, precipitated during neutralization, also remove oxy-anions of transition metals through a combination of intercalation and adsorption of the anionic species on the external surfaces. Layered double hydroxides (LDHs) have been investigated for many years as host materials for a range of anion exchange intercalation reactions. The lamellar structure of LDHs can be used for the controlled addition or removal of a variety of species, both organic and inorganic. This is achieved through their ability to adjust the separation of the hydroxide layers, and the reactivity of the interlayer region. The resultant material adsorbs anions when placed in solution and reverts to the hydrotalcite structure. Significant advances have been made recently on the characterization of these materials, including structural studies on the mechanism of intercalation. The aim of this work was the synthesis and characterizations of LDHs from red mud that will be tested as adsorbent material for heavy metals.